Perayaan Sejit Kongco Ceng Gwan Cin Kun di Kelenteng Tek Hay Kiong dalam Kacamata Fotografi - Bonafix, Dominikus Nunnun; Hartono, Hendrie (Bina Nusantara University, 2014)
Chinese culture is one has formed the Indonesian culture nowadays and has become an integral part of the Indonesian culture. Although it is still originated from their ancestors, Chinese culture in Indonesia has become local and has had assimilation process with other local cultures. In order to preserve the physical structure, documentation in Digital Photography media is important so that this result in highly artistic and prime quality. Photography media is very effective to show visually the Chinese culture in Indonesia, especially in Tegal in details, as well as the artistic side in taking picture technique. It is an early step to introduce old and well preserved culture heritage, especially Chinese culture in Tegal.